Comparative study of different properties of conditioned rice before and after puffing - Biswal, S; Mohapatra, S R; Panda, M K (ORYZA-An International Journal of Rice, 2018)
Puffed rice has got a highest demand both in national and international market. Quality factors such as uniform puffing, contamination free, good color, crispiness etc are the major concern for export of puffed rice. However, the production of puffed rice in India is only limited to village levels. The pre-puffing conditioning (preconditioning) of rice is the most critical factor for achieving the good quality expanded product. It is basically uniform and slow heating of high moisture (water soaked) parboiled grains coupled with turning or agitation. This facilitates proper structural changes of grains like, surface modifications and hardness, removal of moisture and thus produces highly expanded and smooth surfaced puffed rice. This study gives the comparison study of different characteristics of conditioned rice before puffing and after puffing showing the different changes which occurs physically and structurally.